Servicecapes importance and its impact towards employees’ satisfaction at Alam Maritim (M) Sdn. Bhd. / Mohd Insan Tokshim - Tokshim, Mohd Insan (Faculty of Business and Management, 2010)
Servicecapes was introduced by Boom and Bitner to emphasize the impact of physical environment in which a service process takes place. The impact of physical environment is taken lightly by many organizations without realizing the negative impact towards customer and also employees’ satisfaction. With the growing awareness of each individual towards the importance of servicecapes, organizations must not overlook the impact it gives. Managers have tried numerous ways to ensure that employees’ job satisfaction is at the peak. Though servicecapes may seem as if it is a light problem but certain organizations seem to have high staff turnover rate due to the weak servicecapes implementation within the organization. Thus, Alam Maritim Sdn Berhad must ensure that the organization is also at par with the current servicecapes issue otherwise they would come to serious injuries or complaints and might end up collapsing the company.